2015
DOI: 10.1111/biom.12357
|View full text |Cite
|
Sign up to set email alerts
|

Dose Response Signal Detection under Model Uncertainty

Abstract: We investigate likelihood ratio contrast tests for dose response signal detection under model uncertainty, when several competing regression models are available to describe the dose response relationship. The proposed approach uses the complete structure of the regression models, but does not require knowledge of the parameters of the competing models. Standard likelihood ratio test theory is applicable in linear models as well as in nonlinear regression models with identifiable parameters. However, for many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 47 publications
(69 reference statements)
0
21
0
Order By: Relevance
“…The BMD represents an estimate of the dose corresponding to a specified level of increased response (the benchmark response [BMR]), which is derived from the dose–response curve fitted to data (EFSA, ). The regression method is a mathematical approach to simulate and apply a parametric model with continuous variables, which presumes that the dose is responsible for the response (Dette, Titoff, Volgushev, & Bretz, ). In the present study, NOAEL/LOAEL method and BMD method were both used to derive the recommended HBGV, in this case, TDI for NP.…”
Section: Resultsmentioning
confidence: 99%
“…The BMD represents an estimate of the dose corresponding to a specified level of increased response (the benchmark response [BMR]), which is derived from the dose–response curve fitted to data (EFSA, ). The regression method is a mathematical approach to simulate and apply a parametric model with continuous variables, which presumes that the dose is responsible for the response (Dette, Titoff, Volgushev, & Bretz, ). In the present study, NOAEL/LOAEL method and BMD method were both used to derive the recommended HBGV, in this case, TDI for NP.…”
Section: Resultsmentioning
confidence: 99%
“…This is addressed as LR contrast test in their paper (Dette et al, 2015). They use likelihood ratio test instead of the test used in the PoC testing step.…”
Section: Methods Based On Lr Contrast Test (Mclra)mentioning
confidence: 99%
“…But it is well known that classical asymptotic theory are not applicable when parameters are unidentifiable under null hypothesis of the above set up (Andrews & Ploberger, 1994;Chernoff, 1954;Davies, 1987;Lindsay, 1995). The derivations are described in detail in the original manuscript (Dette et al, 2015). They have shown that the asymptotic distribution of the likelihood ratio test statistic (1) corresponding to each model can be approximated by a functional of a stochastic process.…”
Section: Methods Based On Lr Contrast Test (Mclra)mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of approaches address model specification uncertainty when the possibility that the model used in a model-based approach might be incorrect (Bornkamp, Bretz, Dette, & Pinheiro, 2011;Bretz, Pinheiro, & Branson, 2005;Dette, Titoff, Volgushev, & Bretz, 2015;Faes et al, 2007;Klingenberg, 2009;Link & Albers, 2007;Morales et al, 2006;Ohlssen & Racine, 2015;Pinheiro, Bornkamp, & Bretz, 2006;Verrier, Sivapregassam, & Solente, 2014). A number of approaches address model specification uncertainty when the possibility that the model used in a model-based approach might be incorrect (Bornkamp, Bretz, Dette, & Pinheiro, 2011;Bretz, Pinheiro, & Branson, 2005;Dette, Titoff, Volgushev, & Bretz, 2015;Faes et al, 2007;Klingenberg, 2009;Link & Albers, 2007;Morales et al, 2006;Ohlssen & Racine, 2015;Pinheiro, Bornkamp, & Bretz, 2006;Verrier, Sivapregassam, & Solente, 2014).…”
Section: Introductionmentioning
confidence: 99%